Islam and State Issues - Zulbilal, Ahmad; Setiawan, Edi; Ghazali, M. Bahri (West Science Islamic Studies, 2025)
This study explores the relationship between conservative Islamic thought and the state in Indonesia, tracing its evolution from early Islamic political ideals to contemporary dynamics within the nation-state. Through a qualitative literature-based analysis, the research examines key historical milestones, including the role of Islam in anti-colonial resistance, the Jakarta Charter debate, the Konstituante period, and the post-Reformasi landscape. Drawing on primary scholarly sources, the study highlights how Islamic values—such as justice (‘adl), consultation (shura), and public welfare (maslahah)—have continually interacted with national political developments. While the formal inclusion of syari’ah within the constitution remains contested, Islam’s influence endures through cultural, educational, and institutional channels. The study concludes that a contextualized and inclusive interpretation of Islam offers significant potential for contributing to national unity, ethical governance, and democratic resilience in Indonesia.